2021
DOI: 10.3389/fpsyt.2021.770647
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Seizure Therapy Compared to Electroconvulsive Therapy for Schizophrenia: A Randomized Controlled Trial

Abstract: Background: Magnetic seizure therapy (MST) is a potential alternative to electroconvulsive therapy (ECT). However, reports on the use of MST for patients with schizophrenia, particularly in developing countries, which is a main indication for ECT, are limited.Methods: From February 2017 to July 2018, 79 inpatients who met the DSM-5 criteria for schizophrenia were randomized to receive 10 sessions of MST (43 inpatients) or ECT (36 inpatients) over the course of 4 weeks. At baseline and 4-week follow-up, the Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The different effects on language function between MST and ECT are consistent with previous studies regarding MDD and schizophrenia . Wang et al reported some language improvement after accelerated MST in patients with MDD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The different effects on language function between MST and ECT are consistent with previous studies regarding MDD and schizophrenia . Wang et al reported some language improvement after accelerated MST in patients with MDD.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies suggested that high-frequency MST (100 Hz) could lead to a better remission rate than low-frequency (25 Hz) and medium-frequency (50 or 60 Hz) MST but a lower reduction of suicidality . The target symptoms and population may affect the association of MST frequency and efficacy, which remains unclear. The electric field induced by ECT parameters has been attributed to antidepressant or cognitive outcomes and brain neuroplasticity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the response rate of ECT for subjects diagnosed with schizophrenia was up to 74% [ 51 ], which was relatively higher than the response rate for MST of 37.5% to 50% [ 23 , 52 ]. However, another RCT found that MST had antipsychotic efficacy similar to that of ECT [ 53 ]. In recent years, MST has appeared to be an essential and interesting treatment option in depression and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent systematic review reported inconsistent findings on the neurocognitive effects of MST in schizophrenia [ 37 ]. For example, Jiang et al found that MST showed significantly less cognitive impairment with regard to immediate memory, language function, delayed memory and global cognitive function when compared to ECT [ 38 ]. Another study reported that MST led to a specific deficit in the Autobiographical Memory Inventory-Short Form (AMI-SF) without affecting other cognitive domains [ 39 ].…”
Section: Discussionmentioning
confidence: 99%